Impact of diabetes on vasculature: focus on nervous system - Skljarevski, Vladimir; Veves, Aristidis (Current diabetes reviews, 2005)
Chronic complications of diabetes mellitus represent a major cause of morbidity and mortality among those affected and have an enormous impact on society as a whole. Although these complications manifest as a number of clinically distinct syndromes, the pathology underlying them may be very similar, if not identical. Endothelial dysfunction leading to microcirculatory insufficiency and functional ischemia of tissues are proposed to play a pivotal role in the process of their development and progression. Diabetic complications affecting the nervous system occur not infrequently and may have disastrous consequences. This article reviews diabetic complications affecting central and peripheral nervous systems, focusing on similarities in their underlying microvascular pathology and discussing aspects of potentially successful therapeutic interventions. In addition, the article draws a parallel between microvascular dysfunction observed in persons with overt diabetes and those at risk for it.